PENGARUH MOTIVASI BELAJAR, TEMAN SEBAYA TERHADAP PROKRATINASI AKADEMIK DAN PRESTASI BELAJAR MAHASISWA PENDIDIKAN EKONOMI UNIVERSITAS NEGERI PADANG - Muthia Yulianda; Rita Syofyan (Jurnal Ecogen, 2018)
The  purpose  of  this  study  is  to  determine  the  effect  oflearning motivation, peers  on  academic procrastination and student learning achievement of student of the Departemen of Economic Education, State University of  Padang. This  research  is  causative. The  population of  this  study  are  students majoring in Economics Education, State University of Padang 2014, 2015 and 2016years a namber 337 students and obtained as many samples 77 students by using a formula proportional random sampling. The analytical method used is path analysis using SPSS version 21. The results of this study indicate that (1) peers contribute to the learning motivation, (2) learning motivation, peers contribute simultaneously and significantly to the academic procrastination and (3) learning motivation , academic peers and procrastination contribute simultaneously and significantly to the learning achievement. The implementation from this Economic Education students will improve their motivation to learn and interact with peers and not take action to postpone doing assignments so that students of Economic Education can improve learning achievement optimally. Keywords: learning motivation, peers, academic procrastination, and learning achievemen